Order domain beamforming for the acoustic localization of rotating machinery under variable speed working conditions. (30th March 2023) - Zhang, Chenyu; Wang, Ran; Yu, Liang; Xiao, Youhong
Highlights: Oder domain beamforming is proposed for the localization of rotating machineries under variable speed conditions. A steering vector of order domain beamforming is constructed. Abstract: Rotating machinery is widely used in the modern industry, which undergoes huge amounts of variable speed working conditions. Localizing the sound sources of the rotating machinery on a specific order is significant to noise source identification and fault diagnosis. The order domain beamforming method (ODBF) is proposed in this paper to localize the source in the rotating machinery at a specific order. Firstly, the measured acoustic array signals are resampled into the angle domain via the key phase signal. Then, the fast Fourier transform is operated to obtain the acoustic pressure on a specific order. Finally, with the derivated steering vector in the order domain, the proposed order domain beamforming method can obtain the acoustic map on the scanning plane to localize the primary acoustic sources of the rotating machinery. The numerical simulation investigates the performance of the proposed ODBF under different cases. The industrial motor noise source identification experiment further verifies the effectiveness of the proposed ODBF.